Evaluation of epoxy asphalt rubber with silane coupling agent used as tack coat for seasonally frozen orthotropic steel bridge decks. (30th April 2020) - Huang, Qibo; Qian, Zhendong; Chen, Leilei; Zhang, Meng; Zhang, Xiaorui; Sun, Jian; Hu, Jing
Highlights: Epoxy asphalt tack coat modified by silane coupling agent surface-treated rubber particles (ARP) is proposed. The ARP can improve the pull-off failure resistance and water tightness of EAAR tack coat. The ARP can significantly improve the shear failure resistance of EAAR tack coat at low-temperature. EAAR tack coat has superior resistance to recurrent freeze-thaw cycle damage. Abstract: To improve the durability of tack coat applied to orthotropic steel bridge decks against freeze-thaw cycle in seasonally frozen regions, an epoxy asphalt (EA) tack coat modified by silane coupling agent surface-treated rubber particles (ARP) is proposed. In comparison with epoxy asphalt and epoxy asphalt rubber (EAR), the performance of ARP modified epoxy asphalt (EAAR) and EAAR tack coat were evaluated by conducting an experimental program in the laboratory. The properties of studied tack coat binders were first evaluated by viscosity, direct tensile and bending beam rheometer tests. Furthermore, the steel-asphalt interface performance including pull-off, shear and freeze-thaw damage resistance were evaluated as well. Results show that the incorporation of ARP can improve the mechanical properties and freeze-thaw damage resistance of EAAR, but it had shown a negative effect on the allowable construction time. When EAAR tack coat was used, the low temperature pull-off and shear strength can be improved to approximately 1.2 times that of EA tack coat, and the average interface fracture energy of the EAAR tack coat was about twice higher than EA tack coat. Moreover, EAAR tack coat had shown higher freeze-thaw damage resistance than EA tack coat, regardless of the higher nominal seepage pressure ratio, higher shear strength ratio and lower freeze-thaw damage ratio at the same freeze-thaw cycle periods. All the above findings indicate that the EAAR is of great potential to be applied as tack coat for seasonally frozen orthotropic steel bridge decks.